Stereotypes and prejudices in pre-service physical education teachers towards immigrants - Pastor-Vicedo, J.C.; Contreras-Jordán, O.R.; Gil-Madrona, P.; Cuevas-Campos, R. (Cuadernos de Psicología del Deporte, 2016)
The purpose of this study was to nd out which stereotypes pre- vail in future Physical Education (PE) teachers when asked about immi- grant population and to see if within that stereotype, there are subtle or blatant racist attitudes, as well as egalitarian attitudes. A sample of 2524 volunteer pre-service Physical Education teachers (PPET) was used to par- ticipate in this study. A questionnaire on Racist Stereotypes in Ini- tial Training of PE Teachers and a Subtle and Blatant Prejudice Scale were used. Descriptive, univariate and multivariate statistics were used to analyse the information gathered. e data showed PPET with a false tolerant stereotype, where the contextual variables gender and religious preference were crucial, since the boys respect girls, as well as Catholics regard non-believers or other religions, they are reected less egalitarian stereotypes.